Provision of Gas Engine Bus Performance with Air-Fuel Mixture - KULAKOV, Alexandr; GATTAROV, Ilmir; FROLOV, Alexey (Journal of Environmental Management and Tourism; Vol 6 No 1 (2015): JEMT Volume VI Issue 1(11) Summer 2015, 2016)
To evaluate air ratio impact on the engine temperature condition, environmental and economic performance, in-operation and bench test of gas engines with an exhaust gas catalyst have been performed. Air-fuel mixture was adjusted with adjustment of a fuel supply ECU. Data given shows us air-fuel impact on environmental and economic performance as well as reliability of a gas engine.
Keywords: Pollutant emissions; gas engine; catalyst; concentration; exhaust gases; air-fuel mixture; compressed natural gas (CNG)